IMPLEMENTASI ETIKA BISNIS ISLAM PADA PENJUAL BAHAN LAUNDRY DI BANYUWANGI - Suprapto, Ribut; Mamlukah, Mamlukah; Feriawati, Istianah Feriawati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study aims to analyze comprehensively and thoroughly about the application of business ethics applied by sellers of laundry materials in Banyuwangi Regency and to determine the implementation of Islamic business ethics applied by sellers after applying the principles of Islamic business ethics. The results of this study indicate that sellers of laundry materials in Banyuwangi already know about Islamic business ethics and apply them and in carrying out their business adhere to the teachings that have been exemplified by the Prophet who trades with the attitude of sidiq, amanah, fatonah, tabligh in this case not only seeking profit but seeking the pleasure of Allah SWT. Based on the results of the research conducted, it can be concluded in this study that the seller of laundry materials in Banyuwangi Regency is they run their business using Islamic business ethics while maintaining quality and service to customer satisfaction, so that the business can run smoothly, besides that the objects in the research are the Madania Fresh laundry material store, Anggun Fresh laundry material store and Jaya Mulya laundry material store in selling laundry materials already applying Islamic business ethics and according to Islamic economic principles.